Selection of High Affinity Peptides Against Hepatitis B Core Antigen from a Phage-Displayed Cyclic Peptide Library - Ho, Kok Lian (2002)
Hepatitis B virus is the prototype member of the family Hepadnaviridae which causes acute and chronic liver diseases worldwide. The viral nucleocapsid containing a partially double stranded DNA is surrounded by an envelope comprises three distinct but related surface proteins (HBsAg), termed as small (S), medium (M) and large (L)-HBsAg. The essential subunit of the nucleocapsid is a polypeptide comprising 183 amino acids known as core protein (HBcAg). HBcAg produced in Escherichia coli is capable of self-assembly into core-like particles and can be purified easily with ammonium sulphate precipitation and sucrose gradient centrifugation. Core particles make of full-length HB cAg were used as substrate in biopanning with a cysteine constrained phage-displayed heptapeptide library. The most frequently identified phage clones displayed the cyclic peptides C-WSFFS NI-C and C-WPFWGPW-C. The relative dissociation constant (Krl) values for the interaction between the p hages and HBcAg were determined by an equilibrium binding assay in solution. The Kiel values for phage bearing peptides C-WSFFSNI-C and C-WPFWGPW-C for full-length and truncated HBcAg are less than 10 and 30 nM, respectively, which are 17- and 7- fold stronger than that of phage bearing the l inear peptide LLGRMK. The selected phages were able to compete with monoclonal antibody C 1-5 for a binding site on the surface of core particles, suggesting that the docking site of these phages may partially overlap with the epitope of mAb C 1-5, which was mapped at amino acid positions 78 to 83 at the tips of the core particles. The heavy chain of mAb C l-5 is hydrophobic and was proposed to be the contact region for HBcAg. Interestingly, the isolated peptides C-WSFFS NI-C and C-WPFWGPW-C are mainly composed of hydrophobic amino acids and may bind to the same region as mAb C l-5. A synthetic linear peptide bearing the sequence WSFFSNI inhibited the binding of L-HBsAg to core particles in vitro with an inhibition concentration (IC₅₀) approximately 9.8 µM. The additional of cysteine residues to both the N- and C-termini of the peptide greatly reduced the solubility of this cyclic peptide, and as a result the IC₅₀ is approximately 20-fold higher than that of WSFFSNI. A suitable recombinant carrier therefore is needed in order to reduce the hydrophobicity of the peptides and subsequently acts as a deli very system for targeting the peptide to virally infected cells.